Association between endoscopic findings of eosinophilic esophagitis and responsiveness to proton pump inhibitors - Sawada, Akinari; Hashimoto, Atsushi; Uemura, Risa; Otani, Koji; Tanaka, Fumio; Nagami, Yasuaki; Yamagami, Hirokazu; Tanigawa, Tetsuya; Watanabe, Toshio; Fujiwara, Yasuhiro (Endoscopy International Open, 2019)
Background and study aims Endoscopic findings of esophageal eosinophilia sometimes localize to small areas of the esophagus. A previous study suggested that pathogenesis of localized-type eosinophilic esophagitis (LEoE) was associated with acid reflux. However, LEoE treatment outcomes have not been studied. We aimed to analyze the clinical and histologic significance of LEoE in comparison with diffuse-type eosinophilic esophagitis (DEoE).Patients and methods This study included 106 patients with esophageal eosinophilia. Esophageal eosinophilia was defined as a condition where the maximum number of intraepithelial eosinophils was ≥ 15 per high-power field. LEoE was defined as an endoscopic lesion confined to one-third of the esophagus: upper, middle, or lower. Esophageal eosinophilia encompassing more than two-thirds of the esophagus was defined as DEoE. We retrospectively compared LEoE and DEoE in terms of clinical characteristics, histologic findings, and proportion of proton pump inhibitor (PPI) responders. Results Of 106 patients, 12 were classified as having LEoE and 94 were classified as having DEoE. The proportion of asymptomatic patients was significantly higher in the LEoE group than the DEoE group (42 % vs 7 %, P < 0.01). In the LEoE group, 10 patients (84 %) had endoscopic lesions in the lower esophagus. The maximum number of eosinophils did not differ between the groups (54 [24 – 71] for LEoE, 40 [20 – 75] for DEoE, P = 0.65). The prevalence of PPI responders was significantly higher in the LEoE group than the DEoE group (100 % vs 63 %, P = 0.01).Conclusion LEoE can be a sign of good responsiveness to PPI therapy.